Metabolomic profiling and its association with the bio-efficacy of Aspergillus niger strain against Fusarium wilt of guava - Gangaraj, R.; Kundu, Aditi; Rana, Virendra Singh; Das, Amrita; Chawla, Gautham; Prakash, G.; Debbarma, Rubin; Nagaraja, A.; Bainsla, Naresh Kumar; Gupta, Navin Chandra; Kamil, Deeba (Frontiers in Microbiology, 2023)
Bio-control agents are the best alternative to chemicals for the successful management of plant diseases. The fungus Aspergillus niger is known to produce diverse metabolites with antifungal activity, attracting researchers to exploit it as a bio-control agent for plant disease control. In the present study, eleven A. niger strains were isolated and screened for their antagonism against the guava wilt pathogen under in-vitro and in-planta conditions. Strains were identified morphologically and molecularly by sequencing the ITS (Internal transcribed spacer), β-tubulin, and calmodulin genes. The strains were evaluated through dual culture, volatile, and non-volatile methods under an in-vitro study. AN-11, AN-6, and AN-2 inhibited the test pathogen Fusarium oxysporum f. sp. psidii (FOP) at 67.16%, 64.01%, and 60.48%, respectively. An In-planta study was conducted under greenhouse conditions with air-layered guava plants of 6 months old (var. Allahabad Safeda) by pre and post-inoculation of FOP. The AN-11 strain was found effective under both pre- and post-inoculation trials. Further, Gas Chromatography-Mass Spectrometry (GC-MS) analysis was carried out to characterize the volatile compounds of the most potential strain, A. niger. Hexane soluble fraction showed the appearance of characteristic peaks of hexadecenoic-acid-methyl-ester (4.41%), 10-octadecanoic-acid-methyl-ester (3.79%), dodecane (3.21%), undecane (3.19%), gibepyrone A (0.15%), 3-methylundecane (0.36%) and citroflex A (0.38%). The ethyl acetate fraction of the bio-control fungi revealed the occurrence of major antifungal compounds such as acetic acid-ethyl ester (17.32%), benzopyron-4-ol (12.17%), 1,2,6-hexanetriol (7.16%) and 2-propenoic-acid-ethanediyl-ester (2.95%), 1-(3-ethyloxiranyl)-ethenone (0.98%), 6-acetyl-8-methoxy-dimethyl-chromene (0.96%), 4-hexyl-2,5-dihydro-dioxo-furan-acetic acid (0.19%) and octadecanoic acid (1.11%). Further, bio-control abilities could be due to hyper-parasitism, the production of secondary metabolites and competition for site and nutrients. Indeed, the results will enrich the existing knowledge of metabolomic information and support perspectives on the bio-control mechanism of A. niger.